What Do Sheikh-Google And Facebook-Mufti Preach? (Theological Issues in the Muslim Blogosphere and Mobile Apps) - Ibragimova, Rezeda Safiullina-; Beloglazova, Inessa (International Journal of Criminology and Sociology, 2021)
The article discusses what the Islamic segment of the Ru.net came to with for the twentieth anniversary of its existence. Using the communication theory of J.Habermas and based on the analysis of Gary Bunt’s work on cybernetic presence of Islam, it is considered how the development of the blogosphere and social networks change the communication and form the special type of Islamic public sphere through the personal pages of preaches - what topics and questions raised and how this commutation formulates the modern Russian Muslim’s vision. The effect of the social and cultural issues of the Muslims rules have been studied in the literature review. The Internet is turning into a kind of platform for expressing theological ideas, notation Mazhabic priorities and functioning models of the Muslim Ummah.